The Factors Influencing Interest in Shopee Pay Later Users in Bengkulu - Alfin Iman Farizqi; Ahmad Soleh; M. Rahman Febliansa (Penerbit Jurnal Indonesia, 2023)
Organizations are static tools or containers. The organization was founded as a container to achieve the goals that have been set. The objectives to be achieved in this study are: To find out whether the speed of approval, increased effectiveness, increased productivity, ability to pay and security simultaneously affect the interest of online loan users. The method used in collecting data for this research is a questionnaire. The method of data analysis in this study is the Multiple Linear Regression Research Instrument Test the Coefficient of Determination of the Hypothesis.Based on the results of this study it was concluded that there is an influence on the speed of loan approval (X1) on the interest in using Bengkulu online loans (Y) There is an effect of increasing effectiveness (X2) on the interest in using Bengkulu online loans (Y) There is an effect of increasing productivity (X3) on the interest in using loans online Bengkulu (Y) There is an effect of the ability to pay (X4) on the interest in using online loans Bengkulu (Y) There is a security effect (X5) on the interest in using online loans Bengkulu (Y) There is a simultaneous influence on speed of approval, increased effectiveness, increased productivity , the ability to pay and security for the interests of online loan users.